Zdenek Nejedly's Adoration of Fibich as Motive for His Attacks on Dvorak - Beveridge, R. David (Musicologica Olomucensia, 2021)
During recent decades historians and musicologists have devoted major attention to the harsh judgments of Zdenek Nejedly regarding Antonin Dvorak, devoting even one whole book to this topic. They have engaged in speculations about the causes of these judgments in the aesthetic, social, and political context of the time. It seems, however, that one of these causes, evidently the original cause and perhaps the main cause, has not yet been identified as such. To recognize it we must be aware that although Nejedly's best-known condemnations of Dvorak come from the time of the ``Battles over Dvorak'' that broke out in 1912, his positions in this matter were essentially fully developed already much earlier, at the very beginning of his career. For example, in 1903 he wrote: ``Dvorak lacked the artistic intelligence to create new forms.'' Critical is the fact that Nejedly denigrated Dvorak even earlier, in his book about Zdenek Fibich published in 1901, where many passages surprise us with assertions that in harmony, in subtle rhythms, in polyphony, in melody, in ``musical technique,'' and in orchestration, inferior to Fibich was not only Dvorak but also the composer best known as Nejedly's hero: Smetana. Nejedly had published part of this book in advance in instalments in a periodical, late in 1900 shortly after Fibich's death, with an introduction that makes even clearer his adoration of this composer not only as an artist (with whom he himself had studied composition) but as a human being, and his bitter conviction that Fibich had not received the recognition he deserved. Later in the book he attempts to explain Dvorak's greater career success by the assertion that his music is ``much simpler'' and that England, which conferred such glory on him, was an ``unmusical'' country. From these observations and others we may conclude that Nejedly felt the need to criticize Dvorak as the one who had received recognition that rightly belonged to Fibich. And in part Nejedly was correct: even if we perhaps think Dvorak was a greater composer, it is indisputable that at the end of the nineteenth century his fame unjustly left Fibich in the shadow-which today is even more the case than then.
Keywords: Zdenek Nejedly; Antonin Dvorak; Zdenek Fibich; Battles over Dvorak